Radiological comparison of the Wuhan and B.1.1.7 variant COVID-19 infection; are there any differences in chest CT scans - DEMİRCİOĞLU, ÖZLEM; KOCAKAYA, DERYA; ÇİMŞİT, CANAN; ÜLGER, NURVER; ÇİMŞİT, NURİ ÇAGATAY (My University, 2022)
Aim: In September 2020, a variant of the SARS-CoV-2 virus was detected in England and it became the dominant type in most of the countries. The clinical behavior of the B.1.1.7 variant COVID-19 infectionis different from the Wuhan type.So we aimed to investigate whether there are any differences in computed tomography (CT) imaging findings of pneumonia caused by COVID-19 variants. Material and Method: 340 patients who admitted to the emergency departmentwith symptoms of dyspnea and chest pain suspecting COVID-19 pneumonia and pulmonary embolism were included in the study. Oncology (n:12) and pediatric (n:8) patients, patients with negative PCR test (n:56), and patients infected with different variant (n:6) were excluded leaving 258 patients grouped into two (B.1.1.7 and Wuhan type) for evaluation of CT findings such as pleural thickening,pleural and pericardial effusion, consolidation, GGO presence and distribution, upper lobe involvement, pulmonary embolism, tree in bud pattern, centrilobuler nodule, revers halo sign, and hepatosteatosis. Results: A statistically significant difference was obtained between the two groups in terms of pleural thickening (p=0.020), upper lobe involvement (p=0.037), localization of GGO (p=0.001), presence of pleural effusion (p=0.025), embolism (p=0.011) and presence of consolidation (p=0.042). However, no significant difference was found for the development of hepatosteatosis (p=0.520). Conclusion: There aredifferences in radiological findings between B.1.1.7 variant and Wuhan type. In our study atypical radiological findings are more common in B.1.1.7 type. In addition, radiological findings that seen in severe COVID-19 pneumonia are more common in B.1.1.7.
Keywords: COVID-19; Wuhan type; B.1.1.7 variant; tomographic differences; tomography